Evaluation of optimum building envelope materials in different climate regions of Turkey - YİĞİT, SADIK (My University, 2018)
Energy-related issues have been in the centre of the policies of many governments. Increasing the energy production or decreasing the energy consumption can provide significant economic support to countries. Thus, developments in energy industry are of prime importance for countries, especially for Turkey, where improving the energy efficiency is one of the key components of the 2023 national strategy objectives and energy policies. Energy efficiency in residential buildings can be obtained by a number of ways such as optimizing the building envelope. Design of a building envelope depends on a number of parameters including the window, wall, basement, and ceiling properties. The insulation properties of such components can radically impact the energy efficiency of a building. Selecting the optimum materials in designing the building envelope has been one of the fundamental issues in the academic field in the last decade. Providing cost efficient envelope design while satisfying relevant standards has been the common goal. The aim of this study is to find optimum materials for the building envelope design of a residential building in Turkey. Genetic algorithm is utilized for the optimization purposes. The decision variables are determined as the window type and the insulation materials to be applied on the exterior walls, ceiling, and basement. The properties and costs of the materials are obtained from the unit price list prepared by Republic of Turkey Ministry of Environment and Urbanization. The objective function is expressed as the minimization of the total cost of the building envelope materials. The constraints are stated as the limitations indicated by the Turkish Standard 825 (TS 825), “thermal insulation requirements for buildings”. The optimization environment including the genetic algorithm and heating energy calculations is generated in Matlab. A total of 30, 20, 60, and 27 alternatives are identified for the exterior walls, basement, ceiling, and window types, respectively. Optimum design solutions are determined for four climate regions of Turkey as defined by TS 825. The optimization environment could identify optimum design solution among thousands of combinations for each climate region separately. The optimization environment can be utilized by homeowners or designers to determine the building envelope with minimum cost satisfying the relevant standard. Also, the study is expected to encourage professionals in the construction industry to utilize such optimization tools to deal with design-related decisions.